ANALISIS SISTEM INFORMASI AKUNTANSI (SIA) PENGGAJIAN KARYAWAN PADA KANTOR ADMINISTRASI PERUMAHAN THE GAYUNGSARI KOTA SURABAYA - Risxa Ayu; Miya Dewi Suprihandari (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
This research was conducted to provide an overview of the area and evaluate the wage or payroll accounting information system at the Housing Administration Office of The Gayungsari. This research also aims to propose improvements to problems that are then found to support the effectiveness of internal control. The type of research used is qualitatively disqualified. Primary data collection techniques are obtained by interviewing methods to direct sources, namely the Treasurer and Housing Administration Staff of The Gayungsari; secondary data is received by library study methods, and documentation of Miles and Huberman's concepts with data condensation, comparing between theory and practice, and drawing researchers use conclusions as data analysis techniques. The conclusions of this study show that the accounting information system & payroll or wage procedures that have been implemented in the Housing Administration Office of The Gayungsari have not been good enough, and internal control has not been effective enough with the double position